Early life adversity, reproductive history and breast cancer risk. Issue 1 (23rd August 2022) - Boddy, Amy M; Rupp, Shawn; Yu, Zhe; Hanson, Heidi; Aktipis, Athena; Smith, Ken
Abstract: Background and objectives: Individuals who experience early life adversity are at an increased risk for chronic disease later in life. Less is known about how early life factors are associated with cancer susceptibility. Here, we use a life history framework to test whether early life adversity increases the risk of breast cancer. We predict that early life adversity can shift investment in somatic maintenance and accelerate the timing of reproduction, which may mediate or interact with the risk of breast cancer. Methodology: We use population-wide data from the Utah Population Database (UPDB) and Utah Cancer Registry, leading to 24 957 cases of women diagnosed with breast cancer spanning 20 years (1990–2010) and 124 785 age-matched controls. We generated a cumulative early life adversity summation score to evaluate the interaction (moderation) and mediation between early life adversity, reproductive history and their association with breast cancer risk. Results: Our analyses led to three key findings: (i) more early life adversity, when considered as a main effect, accelerates the time to first birth and death, (ii) early age at first birth and high parity decreases the risk of breast cancer and (iii) we find no association between early adversity and breast cancer risk either as a main effect or in its interaction with reproductive history. Conclusion and implications: Early adversity elevates the risk of overall mortality through mechanisms other than breast cancer risk. This suggests early life factors can generate different effects on health. Future work should incorporate more complex view of life history patterns, including multiple life stages, when making predictions about cancer susceptibility. Lay Summary: Previous work has shown that childhood adversity can contribute to poor health later in life. We tested whether childhood adversity was associated with increased risk of breast cancer in US women. We found that childhood adversity was associated with earlier age at first birth but not higher breast cancer risk.